Evaluation of Total Phenolic Content, Total Flavonoid Content, and Free Radicals Scavenging Activity of Syzygium polyanthum Wight. Leaves - Yandy Efrianna Ramadhan; Kevin Awidarta; Agung Endro Unugroho; Abdul Rohman (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2026)
Bay leaves plant (Syzygium polyanthum Wight), from the Myrtaceae family, are traditionally used for their medicinal properties due to bioactive compounds like phenolics, flavonoids, and steroids with antioxidant activity. This study aimed to evaluate the antioxidant potential of bay leaf extract by measuring total phenolic and flavonoid content and assessing free radical scavenging activity. Fresh leaves were collected in Yogyakarta in December 2024, dried, and extracted via methanol maceration, followed by fractionation with n-hexane, ethyl acetate, and aqueous solvents. The Folin-Ciocalteu method was used to measure total phenolic content,iusing gallic acid asiaireferenceistandard, irevealing high phenolic levels, particularly in the ethyl acetate fraction (198.20 ± 0.42 mg GAE/g). The Folin-Ciocalteu method was used to measure total phenolic content, using gallic acid as a reference standard, showing significant flavonoid levels, with the ethyl acetate fraction at 62.06 ± 1.76 mg QE/g. The DPPH assay was utilized to assess antioxidant activity, revealing that the ethyl acetate fraction had the lowest IC50 value (41.71 ±i0.617 µg/mL), demonstrating potent free radical scavenging ability similar to ascorbic acid (9.61 ± 0.138 µg/mL) The ethyl acetate fraction contains a significant amount of phenolics and flavonoids correlated strongly with its antioxidant capacity, highlighting bay leaves as a promising source for herbal medicine development. These findings validate the traditional use of bay leaves and offer updated quantitative data on phenolic/flavonoid levels and antioxidant capacity, highlighting their promise for natural health product development.